COMPARISON OF ANALGESIC EFFICACY OF SYSTEMIC LIGNOCAINE COMBINED WITH DEXAMETHASONE AND LIGNOCAINE INFUSION: Analgesic Efficacy in Advance Cancer Patients - Waseem, Syed Majid; Iqbal, Amjad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the analgesic efficacy of lignocaine combined with dexamethasone and lignocaineinfusion in patients with advance cancer disease.Study Design: Randomized controlled trial.Place and Duration of Study: Pain centre Combined Military Hospital Rawalpindi, from Apr 2016 to Nov 2016.Material and Methods: Total 122 patients, 61 in each group, fulfilling the inclusion criteria were included inthis study after approval of the ethical committee. The technique used was non probability consecutivesampling. Two groups were made; group-A received Lignocaine 2mg/kg and group-B Lignocaine 2mg/kg withdexamethasone 0.15mg/kg in continuous infusion over 30 minutes. Both regimen were administered twiceweekly for a period of 12 weeks as an outdoor procedure. Numerical rating scale used to measure severity ofpain. Baseline and outcome parameters of all patients’ i.e. severity of persistent and breakthrough pain andpercentage relief of pain were recorded and compared at 12 weeks. Mean ± standard deviations were calculatedfor quantitative variables, while qualitative variables presented in frequency and percentages. Chi-square testused for qualitative variables while Independent sample t-test used to compare means. A p-value